Synthesis of α-amino acid derived (1, 2, 3-triazol-4-yl)-picolinamide (tzpa) ligands and their corresponding luminescent Tb(iii) complexes. Issue 8 (21st March 2023) - Hegarty, Isabel N.; Hawes, Chris S.; Gunnlaugsson, Thorfinnur
Abstract : The synthesis of chiral α-amino acid derived (1, 2, 3-triazol-4-yl)-picolinamide (tzpa ) ligands 4–6 designed by combining the coordination properties of two well-known ligand structures within a single unit is described. Abstract : The synthesis of chiral α-amino acid derived (1, 2, 3-triazol-4-yl)-picolinamide (tzpa ) ligands 4–6 designed by combining the coordination properties of two well-known ligand structures within a single unit is described. The self-assembly formation between these ligands and the lanthanide ion Tb(iii ) was investigated in solution by probing the ground and the singlet excited state properties of the ligands as well as monitoring the evolution of the Tb(iii ) emission at long wavelengths. The spectroscopic results showed that while under thermodynamic control the 1 : 3 (Tb : L) is produced, then analysis of the titration data using non-liner regression analysis demonstrated that the main species in solution is the 1 : 2 (Tb : L) after the addition of 0.5 equivalents of Tb(iii ).